Role of Leptin in Iraqi Male Infertility - Batool A. Al-Haidary (Journal of Global Pharma Technology, 2016)
Background: Many etiological factors participate in initiation and development of males’ infertility. Leptin is an adipokine that play a crucial role in obesity and many other biological effects. One of these its effects are on Hypothalamus and Pituitary glands to which males’ infertility may be attributed. Aims of Study: This study was designed to investigate the role of Leptin and its’ receptor in development of infertility among Iraqi males Materials & Methods: Seventy sub-fertile males were included in this investigation to estimate Leptin and its receptor levels in seminal plasma by ELISA techniques. All patients had been diagnosed as a sub-fertile male under the supervision of consultant physician. Seminal fluid analysis was performed for each patient. Body mass index for each patient was calculated besides sera LH, FSH and testosterone hormones determinations and the results of the above tests were compared with those for 30 normal fertile men who matched the patients in their ages. All data has been analyzed statistically. Results: The results revealed highly significant decline in the mean of leptin levels (27.283±3.034ng/ ml) among patients in comparison with healthy fertile control group (47.975±7.152 ng/ ml) (P=0.002). Moreover, LH hormone showed an increment in its mean level (34.699±1.594) in highly significant manner in comparison with control group (14.859±1.947) (P= 0.001). This study referred to highly significant correlation between leptin receptor and BMI (P=0.0001), in addition to significant correlation with testosterone (P=0.046). Meanwhile significant correlation was observed between leptin and FSH (P=0.027). Conclusion: In view of the above results it can be concluded that there is an association between Leptin and FSH which in turn significantly correlated with sperms’ count and theirs ’motility.Keywords: Leptin, Obesity, Sex hormones, LH, FSH, Testosterone, Seminal fluid analysis.